The molecular basis of α-thalassemia. - Higgs, DR (2013)
The globin gene disorders including the thalassemias are among the most common human genetic diseases with more than 300,000 severely affected individuals born throughout the world every year. Because of the easy accessibility of purified, highly specialized, mature erythroid cells from peripheral blood, the hemoglobinopathies were among the first tractable human molecular diseases. From the 1970s onward, the analysis of the large repertoire of mutations underlying these conditions has elucidated many of the principles by which mutations occur and cause human genetic diseases. This work will summarize our current knowledge of the α-thalassemias, illustrating how detailed analysis of this group of diseases has contributed to our understanding of the general molecular mechanisms underlying many orphan and common diseases.